Genome-Wide microRNA Binding Site Variation between Extinct Wild Aurochs and Modern Cattle Identifies Candidate microRNA-Regulated Domestication Genes - Braud, Martin; Magee, David A.; Park, Stephen D. E.; Sonstegard, Tad S.; Waters, Sinead M.; MacHugh, David E.; Spillane, Charles (Frontiers in Genetics, 2017)
The domestication of cattle from the now-extinct wild aurochs (Bos primigenius) involved selection for physiological and behavioral traits, with underlying genetic factors that remain largely unknown. Non-coding microRNAs have emerged as key regulators of the spatio-temporal expression of target genes controlling mammalian growth and development, including in livestock species. During the domestication process, selection of mutational changes in miRNAs and/or miRNA binding sites could have provided a mechanism to generate some of the traits that differentiate domesticated cattle from wild aurochs. To investigate this, we analyzed the open reading frame (ORF) DNA sequence of 19,994 orthologous protein-coding gene pairs from extant Bos taurus genomes and a single extinct B. primigenius genome. Using this data from 19,994 gene pairs, we identified miRNA binding site polymorphisms in the 3' UTRs of 1,620 orthologous genes. These 1,620 genes with altered miRNA binding sites between the B. taurus and B. primigenius lineages represent candidate domestication genes. Using a novel Score Site ratio (SSr) metric we have ranked these miRNA-regulated genes according to the extent of divergence between miRNA binding site presence, frequency and copy number between the orthologous genes from B. taurus and B. primigenius. This provides an unbiased approach to identify cattle genes that have undergone the most changes in miRNA binding (i.e. regulation) between the wild aurochs and modern-day cattle breeds. In addition, we demonstrate that these 1,620 candidate domestication genes are enriched for roles in pigmentation, fertility, neurobiology, metabolism, immunity and production traits (including milk quality and feed efficiency). Our findings suggest that directional selection of miRNA regulatory variants was important in the domestication and subsequent artificial selection that gave rise to modern taurine cattle.